EEG based brain signals analysis (scent classification) - Yang, Jiong (2013)
Over the years, Electroencephalogram (EEG) brain signals have been found closely related to human’s physical and biological activities. These include mechanical moves, emotional states, thoughts and the perceiving of external stimuli. A final year project has been conducted to collect and compare human brain signals between relaxation and scent stimulation and between different scent stimulations as well. Lavender and peppermint scents were used in this project. This report aims to present in detail the design and conduction of the EEG wave collection experiment and the analyses on the collected signals.